Determination of Six Major Compounds in Shaoyao-Gancao-Tang and its Single Herb Decoctions - Gan, P.P.; Zhong, M.Z.; Huang, X.; Sun, M.; Wang, Y. (Asian Journal of Chemistry, 2010)
Shaoyao-Gancao-Tang is a traditional Chinese formula containing Radix paeoniae alba and Radix glycyrrhizae. An ultra performance liquid chromatography-photo diode array detection method was employed for simultaneous quantitative determination of major constituents i.e., gallic acid, albiflorin, paeoniflorin, benzoic acid, glycyrrhizin and liquiritigenin in Shaoyao- Gancao-Tang and its single herb decoctions. Chromatographic separation and determination were performed on an Acquity UPLC BEH C18 (100 mm × 2.1 mm, i.d., 1.7 μM) column by gradient elution using a mobile phase of acetonitrile-0.5 % aqueous acetic acid at a flow rate of 0.3 mL/min. The method was validated for selectivity, linearity, sensitivity, precision, accuracy and stability. It was successfully applied to the comparison of quantification of major active components between Shaoyao-Gancao-Tang and its single herb decoctions. The concentrations of gallic acid, glycyrrhizin and liquiritigenin increased and that of albiflorin, paeoniflorin and benzoic acid decreased significantly (p < 0.01). The experimental data indicated that drug interactions during decocting process could result in the changes of the amount of active components.